Disruptive Technology: The Future of SMS Technology - Cik Ku Haroswati Binti Che Ku Yahaya; Murizah Kassim; Hasnorhafiza Husni (Institute of Advanced Engineering and Science, 2018)
The research illustrates a view on the current trends in the telecommunication industry focusing on the matter of Short Message Service (SMS) technology. It targets and explains disruptive technology and also introduces disruptive technology in Short Message Service (SMS). The methodology of this research is market trend analysis using data on volume of Short Message Service (SMS) sent and received through a mobile network and a survey that was conducted with questionnaires. The findings are Short Message Service (SMS) is predicted to become obsolete and be disrupted by Over the Top (OTT) messaging application by the third quarter of the year 2020. This was implemented with linear regression prediction. By the survey a new trend of using Short Message Service (SMS) has emerged but users have certainly moved away from SMS and now prefer texting Over the Top (OTT) messaging applications.